Role of Purifying Agents in Chemical Transformation of Sulphur: An Ayurvedic Perspective - U. Kamath, Sushant; Pemiah, Brindha; K. Sekar, Rajan; Krishnaswamy, Sridharan; Sethuraman, Swaminathan; Maheswari Krishnan, Uma (Asian Journal of Chemistry, 2014)
Sulphur, one of the key ingredients in Ayurvedic formulations has been used as a single drug or in combination with metals to treat various diseases. Classical Ayurvedic texts describe purification techniques for sulphur as well for metals used in combination with sulphur. Butter is used to melt sulphur and the molten sulphur is quenched in milk to bring about an allotropic transformation. Elemental analysis revealed increase in calcium, potassium, phosphorus and sodium content in sulphur which gets incorporated from milk. A substantial increase in carbon, hydrogen and nitrogen content in the sulphur samples indicated incorporation of carbohydrate, protein and lactose content from milk. This was corroborated with decrease in protein and lactose content in the milk after quenching. The process of quenching with water did not result in an allotropic transformation, confirming that milk is responsible for this chemical change. The allotropic modification is necessary to facilitate further reactions of sulphur through mechanochemistry.